Yield Spread as a Leading Indicator of Real Economic Activity : An Empirical Exercise on the Indian Economy - Goyal, Rajan (IMF Working Papers; Working Paper, 2002)
There is growing evidence that the yield spread could serve as a leading indicator of real economic activity. This paper is an attempt to test this hypothesis for the Indian economy by relating movements in the yield spread in the government securities market to movements in the index of industrial production. The results show that yield spread could, inter alia, be considered as a leading indicator of industrial activity in India.